Sports contingent markets in Port Harcourt metropolis: challenges and prospects with instances from China - Ekpo, Geraldine Umoh Amba; Azunwena, Samuel (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
This study situates its claim on China as the third-leading sports and recreational industry in the world. Based on its mainstay in manufacturing economics and lifestyle, the study argues that sports-contingent markets with recreational activities can thrive faster in high-metropolitan cities. Drawing its inference from China on recreational activities, the paper claims that the same can be replicated in Port Harcourt Metropolis, considering the population growth of the city. In other words, the secondary statistics under study showed that highly populated cities need recreational industries as a way to help manage therapeutic issues associated with stress-borne activities. As well, the statistics under study showed that recreational industries in high-profile cities with population imbalances can form small-scale businesses for young athletes. Hence, in 2020 the market size of China in sports and recreational activities was estimated at three trillion yuan, contributing 1.2 percent of the country's GDP of the year. This is generated by local sports venues that attract visitors to recreational communities. Primarily, in comparison of the population growths in Port Harcourt Metropolis as one factor observed from the statistics under study, the paper concludes the need for the state and private individuals to invest in sports contingents markets.